2023
DOI: 10.1111/jbi.14594
|View full text |Cite
|
Sign up to set email alerts
|

Habitat heterogeneity determines species richness on small habitat islands in a fragmented landscape

Abstract: Aim The small‐island effect (SIE), as an exception to the species–area relationship, has received much attention in true island systems. However, the prevalence and related patterns of the SIE have not been well evaluated in habitat island systems. Here, we aimed to identify the existence of SIE for habitat islands in fragmented landscapes and determine the key factors influencing species richness on small habitat islands. Location Inner Mongolia Autonomous Region, China. Taxon Vascular plants. Methods Based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 93 publications
0
15
0
Order By: Relevance
“…Farmlandd is the dominant matrix type in this area, accounting for about 30.6 % of the total area, with the main crops grown being potatoes and maize. Further background information about the study area is described in our previous papers ( Yan et al, 2022; Yan et al, 2023; Yan et al, 2021; Zhang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Farmlandd is the dominant matrix type in this area, accounting for about 30.6 % of the total area, with the main crops grown being potatoes and maize. Further background information about the study area is described in our previous papers ( Yan et al, 2022; Yan et al, 2023; Yan et al, 2021; Zhang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…To do so, we first used the moving window method (window size: 500-m radius buffer) to quantify grassland amount and the four landscape indices (patch density, edge density, mean patch area, and mean nearest-neighbor distance metric) surrounding all grassland cells. The 500-m radius buffer was used because our previous studies showed this buffer includes the optimal scale of spatial processes influencing grassland plant diversity in this region ( Yan et al, 2022; Yan et al, 2023; Zhang et al, 2021 ). Second, to quantify the fragmentation per se level, we derived the first principal component (PC1) of the four landscape indices ( Hertzog et al, 2019; Rolo et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggest small habitat islands are hotspots of biodiversity conservation in fragmented landscapes (Wintle et al., 2019; Yan et al., 2021). However, within the limits of the SIE, species richness is independent from the direct effects of the usual explanatory variables, such as area and isolation (Triantis et al., 2003; Triantis & Sfenthourakis, 2012; Yan et al., 2023). Thereby, studies of the SIE could shed new light on the exploration of alternative variables to build up a more predictive and process‐based science of species richness variation across true and habitat island systems.…”
Section: Introductionmentioning
confidence: 99%
“…Since PDARs and FDARs can be explored within the same statistical framework as SARs, where the response variable S is a substitution of phylogenetic diversity or functional diversity (Helmus et al., 2007; Helmus & Ives, 2012; Smith et al., 2013), the exploration of SIEs in PDARs and FDARs is relatively straightforward. However, to date, the majority of SIE studies are focused on taxonomic diversity (Gao & Perry, 2016a; Yan et al., 2023; Yu et al., 2020), but rarely attempted in PDARs (but see Matthews et al., 2020) or FDARs.…”
Section: Introductionmentioning
confidence: 99%